Pengaruh Tingkat Kemampuan Gambar Bunga Mawar melalui Video Tutorial dari Youtube pada Siswa SMP Muhammadiyah 1 Medan Kelas VIII di Medan Sumatera Utara - Annisa Annisa; Sugito Sugito (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to prove the effect of using video tutorial media via YouTube on the level of skill in learning to draw roses in class VIII of SMP Muhammadiyah 1 Medan, North Sumatra. This research uses a quasi experimental research method. With a sample of 60 class VIII students taken using the cluster random sampling technique. This research involved a control class group (drawing using conventional techniques) and an experimental class group (drawing using video tutorials). Based on the research results, the average pretest score for the experimental and control classes was 61 and 64 and the average posttest score for the experimental and control classes was 81 and 74. The results of the calculation of the hypothesis test (t test) showed that Lcount = 0.117 and posttest/tutorial technique Lcount = 0.000. Ltable at the significance level (α) = 0.05 and the number (n) = 60 students is 0.114. This means that the pretest/conventional technique Lcount (0.017) < Ltable (0.114), and the posttest/tutorial technique Lcount (0.000) < Ltable (0.114). It can be concluded that there is a significant influence from the use of video tutorial media via YouTube on the level of skill in learning to draw roses in class VIII SMP Muhammadiyah 1 Medan, North Sumatra.